47 Ketogenic diet in infants with epilepsy (KIWE) – update of recruitment and barriers. (22nd November 2019) - Lyons, Laura; Schoeler, Natasha; Cross, Helen; Eltze, Christin
Abstract : The incidence of epilepsy is greatest in the first 2 years of life. Although data exist for first line treatment of infantile spasms, data are lacking for other epilepsies as well as effective second line treatments for all. The ketogenic diet (KD) is a high-fat, low-carbohydrate diet designed to mimic the effects of starvation on the body. It has been shown to be successful in controlling seizures in several observational studies, and in two randomised controlled trials (RCTs) in older children. No high-quality evidence is available in infants. KD in infants with epilepsy (KIWE) is a multi-centre RTC to determine the effectiveness of the KD on seizure frequency compared to further antiepileptic drug (AED) treatment in children under 2 years with apparent drug resistant epilepsy. The project is currently recruiting at 12 centres across the UK and 6 more are due to be opened by September 2019. Recruitment to this current study remains difficult, but despite numerous barriers, we have achieved 95 recruited patients to date. We discuss the difficulties we've encountered during the study and methods we've used to overcome them.